UJI INKOMPATIBILITAS SOMATIK DAN PERTUMBUHAN JAMUR GANODERMA DARI KEBUN BENIH GENERASI PERTAMA Acacia auriculiformis DI WONOGIRI, JAWA TENGAH - Nurrohmah, SitI Husan; Hidayati, Nur (BBPPBPTH, 2014)
Seed orchard A. auriculiformis F1 at Wonogiri, Central Java has attacked by ganoderma caused root rot. To determine the genetic variation, the pattern of spread of ganoderma necessary to somatic incompatibility test and measure the growth. This study used 8 isolates of the fungus ganoderma. Fungi were grown on PDA (Potato dextrose agar), made parental isolates and paired with each other. The results showed that all pairings indicated incompatible reactions except self pairings. All self-pairings showed compatible reactions that indicated by miycelia merged on PDA forming a single colony. Incompatible reaction zone is characterized by sparse zone, demarcation line and pigmentation. The results of somatic incompatibility test, ganoderma have different genotypes or it is not a single colony. The result indicates that the distribution of root rot in Seed orchard A. auriculiformis F1 at Wonogiri, Central Java not only occured by root to root contact.